The role of art education teachers in using digital technology to teach painting for the middle school stage in Iraq - Kareem Idan Shayea - Ali Lama ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The current research aimed to identify the role of art education teachers in using digital technology to teach drawing for the preparatory stage. The research relied on the descriptive analytical approach to analyze sample models. A questionnaire was prepared according to three axes: the use of digital technology in teaching, the use of programs and applications, administrative and technical. The results of the research found an effective and positive role for the use of digital technology in teaching digital drawing for the preparatory stage according to the three axes, which indicated the great compatibility between paragraphs and standards in general. As for the difference in the statistical function, it was found that there was no difference between the average scores of the sample members attributed to the gender variable, unlike the variables of years of experience and academic qualification, where it was found that there was a difference in the statistical function between the average scores of the sample members for the role of using digital technology in improving digital drawing.